ANALISIS DAMPAK RISIKO PROYEK TERHADAP KINERJA PROYEK (Studi pada Industri Konstruksi di Jawa Tengah Periode Tahun 2001-2010) - Prabawani, Riana Widya (Magister Manajemen, Fakultas Ekonomika dan Bisnis Undip, 2012)
This study aims to examine and analyze the influence of project risk on the project performance in Industrial Construction Services in Central Java. This study used operational risk variable, financial risk variable, hazard risk variable, and strategic risk variable to analyze their influence on the performance of the project. Phenomenon which is found in the implementation of building projects in Central Java is the frequency of deviation between initial planning in terms of time, cost and quality of the results achieved often occurs.Population used in this study was all the companies operating in the field of building construction services in Central Java which listed at Lembaga Pengembangan Jasa Konstruksi and joined in ASKUMINDO (Asosiasi Kontraktor Umum Indonesia), ASPEKNAS (Asosiasi Pelaksana Konstruksi Nasional), APAKSINDO (Asosiasi Pengusaha Kontraktor Seluruh Indonesia), GAPEKNAS (Gabungan Pengusaha Kontraktor Nasional Indonesia), GABPEKNAS (Gabungan Perusahaan Kontraktor Nasional) dan GAPEKSINDO (Gabungan Perusahaan Kontruksi Nasional Indonesia). Sampling technique used in this study was purposive sampling method. Therefore, the sample in this study was determined based on construction services company listed on LPJK (Lembaga Pengembangan Jasa Konstruksi) and domiciled in Semarang, construction service companies that were still in operation during this study period in 2001-2010 and construction services companies that has a minimum of 5 years experience involved in the implementation of construction projects in Central Java during the period of2001-2010. The result of this study showed that operational risk influenced significantly negative towards the performance of the project. On the other hand, financial risk and hazard risk influenced significantly positive towards the performance of the project. While, the risk strategy influenced insignificantly positive towards the performance of the project.